Detection of anxiety symptoms in persons with dementia: A systematic review. Issue 1 (22nd April 2019) - Goodarzi, Zahra; Samii, Leyla; Azeem, Feeha; Sekhon, Ramnik; Crites, Stephanie; Pringsheim, Tamara; Smith, Eric E.; Ismail, Zahinoor; Holroyd‐Leduc, Jayna
Abstract: Introduction: Anxiety is a common symptom for those experiencing dementia and is associated with worse outcomes. The aim of the study was to examine which anxiety tools have been validated compared with a gold standard diagnostic criterion in persons with dementia. Methods: We completed a systematic review of the literature, which was registered a priori with PROSPERO (CRD42016042123). Three databases were searched, MEDLINE, EMBASE, and PsycINFO, as well as the gray literature. Abstracts and full text were searched in duplicate for inclusion. Risk of bias was assessed in duplicate. Results: We identified 9626 citations from all sources after duplicates were removed. Many excluded studies used tools for anxiety, for which no diagnostic accuracy study was identified. Four articles were included in the final synthesis. Included articles had between 32 to 101 participants with mild to moderate dementia. The gold standard criteria focused on either generalized anxiety or all anxiety subtypes. The prevalence of anxiety was between 27.7% and 63.4%. Three tools were examined, the Geriatric Anxiety Inventory, Penn State Worry Questionnaire, and the Rating Anxiety in Dementia (RAID) scale. Sensitivity varied but was the highest in the RAID at 90% and lowest in the self‐rated version of the Geriatric Anxiety Inventory (58%). Discussion: Given how burdensome the symptoms of anxiety are to persons with dementia, valid tools are needed to help identify symptoms. We identified three validated tools, but further validation of these and other tools are needed. Practitioners should consider the use of tools with high sensitivity such as the RAID in persons with dementia.